2006
DOI: 10.3998/ark.5550190.0008.412
|View full text |Cite
|
Sign up to set email alerts
|

Metal-dependant stereoselectivity in the Pauson-Khand cyclization of N-propargyl-γ-amino vinyl sulfones

Abstract: An efficient enantioselective route to N-propargyl-γ-amino vinyl sulfones has been developed, and their Pauson-Khand cyclization has been investigated. The stereoselectivity of the reaction depends both on the structure of the substrate and on the nature of the metal-carbonyl promoter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In order to circumvent the high temperatures and long reaction times necessary to effect the PK cycloaddition, different promoters of the reaction have been widely applied, such as N-methylmorpholine N-oxide, 228 trimethylamine N-oxide, 229 phosphine oxides, 230 alkyl sulphides, 231 thioureas, 232,233 and hard Lewis bases, 234 and it has been found that the selectivity of the reaction depends both on the substrate structure and on the nature of the metal carbonyl/promoter. 235 The cyclization has been also performed as environmentally friendly green protocols, such as in dry-state adsorption conditions, 236 under microwave irradiation, 237,238 in ionic liquids, 239,240 in water, 241,242 and in supercritical ethylene. 243,244 The asymmetric approach to the Pauson-Khand reaction has been efficiently achieved, based on chiral auxiliarydirected π-face discrimination in acetylenic-cobalt carbonyl complexes.…”
Section: Pauson-khand Reactionmentioning
confidence: 99%
“…In order to circumvent the high temperatures and long reaction times necessary to effect the PK cycloaddition, different promoters of the reaction have been widely applied, such as N-methylmorpholine N-oxide, 228 trimethylamine N-oxide, 229 phosphine oxides, 230 alkyl sulphides, 231 thioureas, 232,233 and hard Lewis bases, 234 and it has been found that the selectivity of the reaction depends both on the substrate structure and on the nature of the metal carbonyl/promoter. 235 The cyclization has been also performed as environmentally friendly green protocols, such as in dry-state adsorption conditions, 236 under microwave irradiation, 237,238 in ionic liquids, 239,240 in water, 241,242 and in supercritical ethylene. 243,244 The asymmetric approach to the Pauson-Khand reaction has been efficiently achieved, based on chiral auxiliarydirected π-face discrimination in acetylenic-cobalt carbonyl complexes.…”
Section: Pauson-khand Reactionmentioning
confidence: 99%